Food Distribution Models to Determine Distribution Routes, Distances and Costs - Syaina Ulfa, Azhara; Winarno, Heru (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The agricultural sector is vital to Indonesia’s economy, requiring continuous development to address population growth and technological advancements for increased agricultural production. A persistent challenge lies in the uneven distribution of rice due to inefficiencies in current distribution systems, resulting in supply shortages in deficit areas. To address this, an efficient food distribution model is essential to ensure equitable allocation and delivery. This study develops a distribution model using the Saving Matrix and Nearest Neighbor methods to optimize rice distribution from commodity warehouses to nine storage points in Serang Regency. The proposed model focuses on minimizing costs by determining efficient routes, distances, and resource allocations. The results identify three optimal routes spanning a total distance of 294.5 km, utilizing three towing trucks with a capacity of 45 tons each. Implementation of the model reduces daily distribution costs to IDR. 1,934,866, compared to the previous IDR. 2,785,000, achieving a cost saving of IDR. 940,134 per day. This substantial efficiency improvement demonstrates the model’s potential to address distribution challenges and support equitable rice allocation. By ensuring cost-effective and optimal transportation, the proposed model provides a practical solution to enhance food distribution systems in Indonesia, addressing key issues in agricultural logistics.